Molecular simulation between amyloid beta (1-42), a Peptide associated with alzheimer disease, and zinc(ii) ion - Abdul Ghani, Nur Syafiqah (2016)
Alzhe imer’s disease (AD) is a brain disorder resulting fro m the accu mulation of amyloid-forming (both as amyloid-β and tau). Aβ peptide is present in everyone’s brain, but the amyloid plaques found in AD’s patients are abnormal, as they can degenerate nerve endings. The number of Alzheimer’s patients is increasing rapidly while there are no specific solutions being reported yet to treat AD effect ively. Amyloid-β(1-42) is a major fragment from amyloid precursor protein (APP) which tends to aggregate into mature amyloid fibrils through a number of intermediate structural forms, also called the oligomers or protofibrils. They are toxic to neurons. The mechanis m by which Aβ aggregates in the brain is not fully understood, however there is increasing evidence that metal ions may play an important role in this aggregation process. In a healthy brain, the metal ion content is stringently regulated and the concentration of free metal ions is kept at a very low level. Researchers nowadays are trying to uncover the neurodegenerative role of transition metals and the oxidative stress in AD which has been found to be responsible for major cellular problems. There are a vast number of experiment studies trying to shed some light on these processes but the lack of theoretical studies on this matter is quite visible. Here, we investigated the effect of zinc ion on Aβ (1-42) and its aggregation water and its mixture with hexafluoroisopropanol (HFIP) using molecular dynamics calculations. From our results, the amyloid-β(1-42) fragment and its aggregated structure showed good stability in both conditions which were with and without zinc in water based on the root mean square deviation and radius of gyration calculations over 1 μs and 100 ns simulation time for aggregation process. Besides that, Aβ(1-42) with and without zinc tend to produce more helica l structures in solvent mixtu re, but no α -helix was detected in both Aβ-H2O and Aβ-Zn-H2O models. The fle xibility of Aβ(1-42) in solvent mixture was lower than Aβ(1-42) in water due to the length of its helical structure. In contrast, the presence of metal ion increased the fle xib ility of Aβ(1-42) when the peptide was placed in the solvent mixture, compared to its flexibility in water. Ou r aggregation study showed that 6Aβ-6Zn-HFIP-H2O model had significant changes in secondary structures, compared to 6Aβ -6Zn-H2O system. There was also a good correlation with the low flexibility of peptide in water. In addition, Aβ(1-42) with zinc in water produced less helical structure compared to Aβ (1-42) with zinc in mixed solvent. As shown in secondary structure analysis, the aggregation process occurred rapidly in water after 20 ns compared to solvent mixture where the fully spherical structure was not shown in the mixed solvent.